Digital data: is a new legal regulation needed? - Medvedevaitė, Akvilė; Mickevičiūtė, Gabrielė Velta (Vilnius University Open Series, 2021)
This article analyzes the phenomenon of digital data and its impact on both the daily lives of each individual and businesses. Article discusses the legal issue of data ownership, which is inextricably linked with the emergence of Big data. The EU legal regulation of digital data faces the following shortcomings: i. legal regulation of data does not keep pace with the rapid development of technology and the phenomenon of such large-scale data creation; ii. the current EU data legislation is intended to protect the interests of the data subject or business and not to create a common data regulatory ecosystem. For these reasons, the question of data ownership is raised, which is thought to be able to change the whole legal perception of digital data in the further evolution of the Industrial Revolution.